Integrated Development Model (IMD): A Systematic Review and Reflection - Jordan Tovera Salvador (European Scientific Journal, ESJ, 2016)
This paper evaluates a recognized supervision model and reflects on how this model has affected one’s personal role as an instructional supervisor. Integrated Development Model of Supervision (IMD) is one of the most sought after developmental models of supervision in the past decades and even up to the present. Developmental models of supervision are usually derived from the idea that the supervisee has the capability to develop from novice to expert with the guidance and counseling of the supervisor. Each of the developmental stages of supervision has specific skills and competencies that are notable and observable amongst the supervisee and supervisor. However, just like any other models of supervision, developmental models have loopholes identified by experts such as: (1) these models are simplistic and vague, (2) emphasizing on the amalgamation of the advances to developmental supervisions, (3) no new models of supervision have emerged, (4) does not allow differing routes to development for dissimilar trainees and (5) does not report any waning on the part of the supervisee. IDM was formulated based from the ambiguities of the early developmental models and to answer the gaps in shifting between each developmental stage.